Scattering of high-energy magnons off a magnetic skyrmion - Schroeter, Sarah; Garst, Markus (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
We discuss the scattering of high-energy magnons off a single magnetic skyrmion within the field-polarized ground state of a two-dimensional chiral magnet. For wavevectors larger than the inverse skyrmion radius, krs ≫ 1 the magnon scattering is dominated by an emerging magnetic field whose flux density is essentially determined by the topological charge density of the skyrmion texture. This leads to skew and rainbow scattering characterized by an asymmetric and oscillating differential cross section. We demonstrate that the transversal momentum transfer to the skyrmion is universal due to the quantization of the total emerging flux while the longitudinal momentum transfer is negligible in the high-energy limit. This results in a magnon-driven skyrmion motion approximately antiparallel to the incoming magnon current and a universal relation between current and skyrmion-velocity.